Sensibilizando professoras de creche: a escuta de bebês no contexto da pandemia - Santos, Adriana da Costa (2022)
This research has as its object: The sensitization of teachers to listen to babies in the context of the pandemic and is guided by the following question: How to sensitize educators, in moments of formation, so that they advance in listening to babies? The general objective is to verify how the awareness, on the part of the teachers, of listening to babies in a daycare center in the context of the pandemic occurs. As specific objectives, we outline: Identify what teachers understand by listening; sensitize the educators, in moments of formation, so that they advance in the ability to listen to the babies and how they materialize this concept in the daily life of the institution. We start from the hypothesis that such listening still does not occur in a way that promotes children's protagonism, as educators often have ready-made speeches in defense of listening, but they are unable to effectively carry out it in a transforming way. Even in times of a pandemic, we understand that teachers are able to develop/extend listening, based on their ongoing in-service training, exchanges with their peers and other protagonists, and through intentional records arising from interpersonal relationships with babies and small children in everyday life. of the institution. The research universe is a Municipal School of Basic Education located in the municipality of São Bernardo do Campo - which exclusively attends the daycare stage, and the participants are two teachers and an education assistant from the Nursery class (1 year old babies). The methodology used is qualitative research and the data collection instruments for raising awareness are the life narratives of three educators in the class, three proposals agreed together and the documents produced by them, namely: logbook, book of the life and the individual report of babies. All material collected was analyzed based on Laurence Bardin's content analysis, and the following categories emerged: The absence of teachers' listening as children: transmissive pedagogies and docility of bodies; listening to the participants by their teachers: participatory pedagogies; Babies listening: the multiple forms of expressions; listening during the pandemic during remote service; Teachers' awareness of listening to babies: continuing education in service; authorial pedagogical documentation: teaching actions enhanced by the narratives of listening to babies. As a theoretical framework, we will rely on the ideas of authors of critical pedagogy. The results confirm our hypothesis and point out that for teachers to effectively listen to babies, in order to favor children's protagonism in the daily life of the institution, they need sensitization and permanent in-service training in order to support their positions in defense of the principles present in participatory pedagogies, with theoretical knowledge about the importance of listening, as well as reflective partnerships that also relate to babies inside and outside the institution (other professionals and babies' families) that consider the multiple ways of expressing themselves. These results lead us to think about the complexity present in listening to babies to perform it in a transformative way, especially in times of pandemic.